Hydrothermally synthesized (N,O)-linked Cu(II)-based coordination complex as a potential antibacterial agent - Chettri, Anmol; Pradhan, Sudarshan; Gurung, Pritika; Roy, Sriparna; Sinha, Biswajit (European Journal of Chemistry, 2023)
The N,O-linked Cu(II)-based coordination complex was synthesized hydrothermally and characterized by SC-XRD, FTIR spectroscopy, and FE-SEM. Single crystal X-ray diffraction studies showed that the complex crystallizes in a square pyramidal geometry and belongs to the monoclinic crystal system with the space group P21/n. Crystal data for C14H13CuN3O6: a = 8.7355(11) Å, b = 17.646(2) Å, c = 9.8036(12) Å, β = 98.506(6)°, V = 1494.6(3) Å3, Z = 4, μ(MoKα) = 1.500 mm-1, Dcalc = 1.701 g/cm3, 5120 reflections measured (4.616° ≤ 2Θ ≤ 49.982°), 1953 unique (Rint = 0.0316, Rsigma = 0.0718) which were used in all calculations. The final R1 was 0.0380 (I > 2σ(I)) and wR2 was 0.0972 (all data). The experimental antibacterial activity studies performed using the disc diffusion method revealed that the complex is indeed acting as a good antibacterial agent against Staphylococcus aureus and Escherichia coli. A better understanding of the binding mechanisms was uncovered through comparative molecular docking investigations. The docking score for the target S. aureus glyrase complex with DNA (PDB id-2XCS) was found to be -7.1 kcal/mol, while the docking score for dialkylglycine decarboxylase (PDB id-1D7U) was -5.2 kcal/mol. The high docking score of the complex with the target protein allowed the complex to act as a potential antibacterial agent. These results were also supported by other theoretical studies such as DFT calculations and pharmacokinetic studies. The correlation between the HOMO-LUMO energy gap and antibacterial activity was studied computationally. Hirshfeld surface analysis and pharmacokinetic studies were also performed for this crystal for a better understanding of the intermolecular interactions and ADME properties.